STUDI EFISIENSI PEMANFAATAN NITROGEN EMPAT VARIETAS PADI SAWAH PADA TANAH INCEPTISOL. - A.H. Syaeful Anwar; H. Darjanto (JURNAL AGROTROPIKA, 2009)
The research was conducted in Green House of Agricultural Faculty Jenderal Soedirman University Karangwangkal Village, North Purwokerto Subdistrict, Banyumas Regency. The research was performed at December 2007 until April 2008. Experimental design used was Randomized Complete Block Design (RCBD) that comprised of two factors that were nitrogen fertilization and lowland variety. Nitrogen fertilization comprised of fours level that were 0 kg N/ha (N0), 80 kg N/ha (N1), 160 kg N/ha (N2), 240 kg N/ha (N3), while tested lowland varieties comprised of 4 varieties that were : varieties of IR-66, Indragiri variety, Dusel variety and Padi Halus variety. Research result showed that there was difference of physiological characteristic in utilize nitrogen, difference of nitrogen use efficiency and difference of optimal dose in each tested variety. Nitrogen fertilization increase with increase of crown N absorption and grain N absorption. Highest to lowest nitrogen use efficiency that was IR-66 variety, Indragiri variety, Padi Halus variety and Dusel variety. Optimal dose of nitrogen fertilizer at IR-66 variety was 100 kg N/ha, Indragiri variety was 200 kg N/ha, Dusel variety was 83,3 kg N/ha and Padi Halus variety was 50 kg N/ha.Keywords : efficiency, nitrogen, variety, Inceptisol